1998
DOI: 10.1042/cs0940057
|View full text |Cite
|
Sign up to set email alerts
|

Long- and Short-Term Blood Pressure and Rr-Interval Variability and Psychosomatic Distress in Chronic Fatigue Syndrome

Abstract: 1. Chronic low blood pressure has been associated with fatigue and low mood. However, in the chronic fatigue syndrome (CFS) the blood pressure (BP) and heart rate profile and their variabilities have not been characterized as yet. 2. We performed office and 24 h ambulatory BP recordings in 38 subjects (age, 34.8 +/- 8.0 years) who fulfilled the Holmes criteria for CFS and in 38 healthy control subjects (age 35.6 +/- 10.5 years), as well as short-term beat-to-beat BP and RR-interval recordings for 10 min in sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
24
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 19 publications
7
24
0
Order By: Relevance
“…Freeman et al [9] also could not demonstrate orthostatic hypotension during active standing in CFS patients. This is in agreement with another study in which active standing for 30 minutes did not elicit orthostatic hypotension in unselected CFS patients [26]. However, using a prolonged tilt [pre]syncope) to head-up tilt without isoproterenol administration occurred in 25% [9], 40% [11], 71% [7], or 100% [8] of the CFS patients.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Freeman et al [9] also could not demonstrate orthostatic hypotension during active standing in CFS patients. This is in agreement with another study in which active standing for 30 minutes did not elicit orthostatic hypotension in unselected CFS patients [26]. However, using a prolonged tilt [pre]syncope) to head-up tilt without isoproterenol administration occurred in 25% [9], 40% [11], 71% [7], or 100% [8] of the CFS patients.…”
Section: Discussionsupporting
confidence: 90%
“…The heart rate response during standing tended to be lower in our CFS group, which was not found in other studies [9,26]. The I-E difference was also slightly decreased, which was also found by Freeman et al [9].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…This is in agreement with some [4,9,34,40] but not all [8,41] reports on autonomic cardiovascular regulation in CFS. An increased supine heart rate seems to be consistent with the findings of sympathetic predominance in CFS patients at rest, as has also been estimated from spectral indices of heart rate and blood pressure variability [6,8].…”
Section: S Prevalence Of Oi In Cfs Patientssupporting
confidence: 92%
“…Some studies reported subtle changes in "sympathetic-parasympathetic balance" [4][5][6][7][8][9], indicating alterations in cardiovascular autonomic control in response to orthostatic stress in CFS patients. As a clinical CAR 014 s Abstract Background Data on the prevalence of orthostatic intolerance (OI) in patients with chronic fatigue syndrome (CFS) are limited and controversial.…”
mentioning
confidence: 98%